UAV - Red Green Blue (RGB) Point Cloud (PC) from Laevasvagge UAV from 2021, 2021-08-07 - Tarfala Research Station (Stockholm University, 2023)
Point cloud generated from photos taken from an UAV platform using photo-stereography techniques. Nominal pixel size is 5 cm. The points contain a value for color, from RGB photos.
Tarfala Research Station (2023). UAV - Red Green Blue (RGB) Point Cloud (PC) from Laevasvagge UAV from 2021, 2021-08-07 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/kSfLCzJDFfaK9epf2iFNyUGq
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap